Correlation between total phenolic and flavonoid contents with antioxidant activity of Malaysian stingless bee propolis extract - Asem, Nornaimah; Abdul Gapar, Nur Adilah; Abd Hapit, Nor Hussaini; Omar, Eshaifol Azam (Journal of apicultural research, 2020)
Propolis is considered to contain a variety of polyphenols (flavonoids, phenolic acids and their esters), waxes, steroids and terpenoids and its contents may be influenced by the vegetation at the site of collection as well as the species of stingless bees. The purpose of this study is to investigate the total phenolic and flavonoid content and the correlation that may exist between the mentioned class of compounds and the antioxidant properties. The ethanolic extract of propolis samples were prepared from three different stingless bee species namely Tetrigona apicalis, Heterotrigona itama and Geniotrigona thoracica, collected from one of the bee farms located in Perak, Malaysia. Antioxidant activity of the propolis samples was examined by three different methods which were DPPH, ABTS and FRAP assay. Total phenolic and total flavonoid content were determined by using Folin-Ciocalteu and aluminium chloride colorimetric method, respectively. The result shows that all propolis samples exhibited positive antioxidant activity. Propolis of G. thoracica was found to be the most potent sample in all antioxidant tests. The analysis between total phenolic and flavonoid content of propolis and its antioxidant properties were found to have a strong correlation. These results signify that the potency of propolis derived from different species is variable, depending on the phytochemical contents, thus further study on the specific bioactive compounds would be the area of interest in the near future.